Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fmicb.2016.01992
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotides Induce Differential Cytokine and Chemokine Gene Expression Profiles in Dapulian and Landrace Pigs

Abstract: Oligodeoxynucleotides containing unmethylated CpG motifs (CpG ODN) mimic the immunostimulatory activity of microbial DNA by interacting with Toll-like receptor 9 (TLR9) to activate both the innate and adaptive immune responses in different species. However, few studies have been published to compare the effects of CpG ODN on different pig breeds. Therefore, in this study, whole blood gene expression profiles of DPL and Landrace pigs treated with CpG ODN were studied using RNA-seq technology. Five Hundred diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…It has been reported that TLRs play a vital role in immunity (32). One previous study showed that the expression of TLRs may reflect the status of disease resistance of pigs (33,34). In our study, we found that the mRNA abundance of TLR3, TLR4, TLR6, and TLR8 in FF-fed pigs was significantly higher (P < 0.05), indicating that the FF diet could influence the gene expression of TLRs.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that TLRs play a vital role in immunity (32). One previous study showed that the expression of TLRs may reflect the status of disease resistance of pigs (33,34). In our study, we found that the mRNA abundance of TLR3, TLR4, TLR6, and TLR8 in FF-fed pigs was significantly higher (P < 0.05), indicating that the FF diet could influence the gene expression of TLRs.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, transcriptome analysis was performed and the molecular regulatory mechanisms were explored. As shown in Supplementary Table 1 , the average data volume of each sample reached 2.3 G, and the proportion of base quality reaching Q30 is 94%, which is better than other researches, indicating that quality of sequencing is normal and satisfied the following analysis [ 15 , 16 ]. DEG analysis showed that the number and variation of upregulated and downregulated genes of the two cultivars at different stages have great changes.…”
Section: Discussionmentioning
confidence: 97%
“…RNA-Seq has been used as an effective method for exploring pathology-associated transcriptional changes in peripheral blood in many species, such as human (Liu et al 2014), cattle (McLoughlin et al 2014, and swine (Koltes et al 2015;Hu et al 2016). It has also enabled detailed analysis of the host transcriptome for Salmonella (Kommadath et al 2014) and Streptococcus suis (Wu et al 2014) infections in pig.…”
mentioning
confidence: 99%